Knowledge, Perception, and Willingness to Enrol in a Health Insurance Scheme: A Survey Among Uninsured Persons in Southern Nigeria - Unyime Eshiet; Abasibiangake Sunday; Ikpeme Neto; Joy Umoh; Victor Mba; Blessing Udo (The Journal of Medicine, Law & Public Health)
Background: Out-of-pocket payments for healthcare services hinders the attainment of universal health coverage.